A Modified Consensus Algorithm with a Diminutive of Proof of Longevity - Augmenting the Effectuation of Blockchain - R, Thamarai Selvi; Fernandez, Abigail Christina (International Journal of Computer Sciences and Engineering, 2019)
Blockchain, since its inception in 2009, has fuelled up innovation over a wide spectrum of applications that have beget from the technology and have harvested it manifolds in arenas such as smart contracts, digital currency, decentralised record keeping, securities in terms of crowdfunding and escrow. Bitcoin, the first brainchild of the Blockchain has been fine-tuned furthermore by the impending inflow of the many consensus algorithms that are being introduced by the many researchers, with the intent of making spectacular the impact of the technology, keeping in mind the network parameters, efficiency of the blockchain and optimization in the deployment of a decentralised application over the internet. This paper aims at introducing a novel qualitative framework of consensus algorithm called the Proof of Longevity (PoL), that would improvise the current blockchain in a way so as to rule out adversaries in terms of Node Identity management, computation energy and cost saving and strategize the double spending and selfish mining problems in the real world and to catalyse the blockchain network to its zenith.